2013
DOI: 10.1021/bi400357m
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric DNA-Search Dynamics by Symmetric Dimeric Proteins

Abstract: We focus on dimeric DNA-binding proteins from two well-studied families: orthodox type II restriction endonucleases (REs) and transcription factors (TFs). Interactions of the protein's recognition sites with the DNA and, particularly, the contribution of each of the monomers to one-dimensional (1D) sliding along nonspecific DNA were studied using computational tools. Coarse-grained molecular dynamics simulations of DNA scanning by various TFs and REs provide insights into how the symmetry of a homodimer can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 93 publications
1
35
0
Order By: Relevance
“…One should note that due to the coarse-grained nature of the model, the distances between the charged beads of the protein and of the DNA are longer compared to the fully atomistic models. The effective electrostatic interactions are therefore weaker in our model and correspondingly the effective range of salt concentration (0.01–0.05 M) that allows the protein to interact strongly with the DNA molecule is typically lower compared to the physiological salt conditions (0.1–0.15 M) (32,65,66). Nevertheless, the model has been proven to successfully capture key characteristics of protein search modes on DNA (25,27,29) at salt conditions ranging from 0.01 to 0.2 M. We used a dielectric constant of 70–80, because the protein–DNA interface is much more hydrated in the non-specific complex than in the specific complex (39).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…One should note that due to the coarse-grained nature of the model, the distances between the charged beads of the protein and of the DNA are longer compared to the fully atomistic models. The effective electrostatic interactions are therefore weaker in our model and correspondingly the effective range of salt concentration (0.01–0.05 M) that allows the protein to interact strongly with the DNA molecule is typically lower compared to the physiological salt conditions (0.1–0.15 M) (32,65,66). Nevertheless, the model has been proven to successfully capture key characteristics of protein search modes on DNA (25,27,29) at salt conditions ranging from 0.01 to 0.2 M. We used a dielectric constant of 70–80, because the protein–DNA interface is much more hydrated in the non-specific complex than in the specific complex (39).…”
Section: Methodsmentioning
confidence: 93%
“…Of course, the relative weights of the various search mechanisms are also dependent on the sequence composition and structural features of DBPs (28,32,81). Our results suggest that, for a given DBP, the rotation-coupled sliding dynamics is precluded in highly curved DNA because of the large electrostatic energy barrier between the inside and outside of the DNA molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors are known to search for their sites through some combination of nonspecific DNA binding via threedimensional (3D) diffusion and subsequent sliding across the DNA via one-dimensional (1D) diffusion (Hammar et al 2012;Khazanov et al 2013). However, the extent to which these mechanisms affect transcriptional regulation is not well understood.…”
Section: Figure 2 (Legend On Next Page)mentioning
confidence: 99%
“…It has been suggested that intersegment transfer significantly accelerates the search for a specific target site on DNA under conditions where the protein is adsorbed onto the DNA most of the time, as it is in vivo. [44] The interactions of tetrameric proteins, such as p53, with nonspecific DNA contrast sharply with those of mono-or dimeric p53. Describing the molecular aspects of DNA search is essential for understanding the interplay between the structural architecture of proteins or DNA and the efficiency of the DNA search.…”
Section: Introductionmentioning
confidence: 99%
“…Homodimeric proteins may slide very differently than their monomeric variants. [44] The interactions of tetrameric proteins, such as p53, with nonspecific DNA contrast sharply with those of mono-or dimeric p53. Compared with single-domain proteins, proteins composed of several domains may also show unique biophysical characteristics when interacting with DNA.…”
Section: Introductionmentioning
confidence: 99%